(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
Information security is an important issue in the era of information technology today. Users in a system often use traditional methods as passwords to protect their resources and data. The article mentioned the trend of building a safe and easy-to-use password policy for users in the system such as components, complexity, expiry dates, lock policies and password alerts ...